Keputusan Pembelian Produk Limited Edition: Systematic Review - Herdiati, Meilisa Fani; Iriawan, Andi; Fitriyah, Hadiah (Master of Management Diponegoro University, 2021)
Every company has an effective strategy for determining whether to develop, maintain or even withdraw from the market. With the development of the times, limited edition products are now mushrooming. Limited edition labels are now given not only to antique, exclusive and expensive products such as luxury cars and savings items but also to fast moving consumer goods. This study will analyze a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-analysis method. Searches for research articles relevant to the research topic were carried out on the international journal databases of Springer Link, Science Direct, Emerald, and Wiley using the phrase â€œlimited edition productsâ€. The results show that purchasing decisions are influenced by the factors of scarcity, need for uniqueness, and brand-retailer collaboration. This research is expected to be used as material for consideration by the company to formulate the right marketing strategy.